PRAGMATIC ASPECTS OF BELLE LETTERS TRANSLATION - Ruziyeva Nilufar Jaxongirovna (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
The article explores the pragmatic aspects involved in the translation of belle lettres (literary works), with a particular focus on how meaning, context, and cultural nuances are conveyed from the source language to the target language. It analyzes the challenges that arise when transferring not just the linguistic content but also the stylistic, emotional, and cultural layers embedded in literary texts. Emphasis is placed on the translator’s role as a mediator of communicative intent and how pragmatic equivalence can be achieved through careful interpretation of authorial tone, implied meaning, and literary devices. The study includes comparative analyses of selected translated literary passages to illustrate how pragmatic strategies such as compensation, adaptation, and contextual substitution are applied. This article contributes to a deeper understanding of the delicate balance between fidelity to the original and the need for resonance within the target culture.